SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMBORAN SUMUR MINYAK BERDASARKAN PERHITUNGAN EKONOMI - Herry Sofyan (Jurusan Teknik Informatika, 2010)
Oil represent one of nature resource which is not new but represent the solid industry of capital, technological solid and have the high risk. This matter need system of decision supporter capable to give the economics analysis needed by taker of decision or decision maker to analyse the prospect of development economics well of oil drilling so that can be made by a decision base of whether the oil well competent developed or not. Intention of this system is to give the amenity for user in taking decision of whether an developed competent oil well or not. Hence from that felt important to be designed and develop by system of decision supporter for the drilling of oilwell pursuant to economic calculation. In this system economics parameter used in the form of Net Present Value ( NPV), Rate Of Return ( ROR), Profit To Investment Ratio ( PEAR), and Pay Out Time ( POT). Methodologies used in develop this system method of Water Fall and this system will be develop to use the software Delphi 7.0. This system will give the output in the form of decision base whether competent oil well drilling project to be developed or not pursuant to its economics calculation. Minyak merupakan salah satu sumber daya alam yang tidak terbaharukan namun merupakan industri yang padat modal, padat teknologi dan mempunyai resiko yang tinggi. Hal ini memerlukan suatu sistem pendukung keputusan yang mampu memberikan analisa ekonomi yang diperlukan oleh pengambil keputusan atau decision maker untuk menganalisa prospek keekonomian pengembangan suatu sumur pemboran minyak sehingga dapat dijadikan dasar keputusan apakah sumur minyak tersebut layak dikembangkan atau tidak. Tujuan dari sistem ini adalah untuk memberikan kemudahan bagi user dalam mengambil keputusan apakah suatu sumur minyak layak dikembangkan atau tidak. Maka dari itu dirasa penting untuk dirancang dan dibangun sistem pendukung keputusan untuk pemboran sumur minyak berdasarkan perhitungan ekonomi. Dalam sistem ini parameter keekonomian yang digunakan berupa Net Present Value (NPV), Rate Of Return (ROR), Profit to Investment Ratio (PIR), dan Pay Out Time (POT). Metodologi yang digunakan dalam membangun sistem ini adalah metode Water Fall (air terjun) dan sistem ini akan dibangun menggunakan perangkat lunak Delphi 7.0. Sistem ini akan memberikan output berupa dasar keputusan apakah suatu proyek pemboran sumur minyak layak untuk dikembangkan atau tidak berdasarkan perhitungan ekonominya.